Dampak Penambangan Emas Terhadap Keanekaragaman Makrozoobentos di Sungai Batang Kuantan - Villa Indah Delfia; Yulminarti Yulminarti (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Unlicensed Gold Mining (PETI) is a mining term that does not get permission from the government as the holder of state control rights over mining materials. This almost happened on the entire banks of the Batang Kuantan River, such as Pebaun Hulu Village. This study aimed to analyze the diversity of macrozoobentos in the waters of the Batang Kuantan River. Sampling was carried from in December 2023-January 2024 in the Batang Kuantan River using Ekman Grab and identification was carried out at the Ecology Laboratory of the Department of Biology, FMIPA, University of Riau. The results showed that there was a significant difference in the diversity, uniformity, and composition of macrozoobentos between Station one and Station two in the Batang Kuantan River. Station one showed higher diversity (H' = 1.48) compared to Station two (H' = 0.82), indicating greater species variation at Station one. Similarly, the uniformity (e) of Station one (0.70) is higher than that of Station 2 (0.39), signifying a more even distribution of individuals at Station one. Community similarity analysis (CJ) showed that the two stations had a similarity rate of 0,83 indicating a considerable difference in species composition between the two stations.